Effectiveness of a mobile antiretroviral pharmacy and HIV care intervention on the continuum of HIV care in rural Uganda - Bajunirwe, Francis; Ayebazibwe, Nicholas; Mulogo, Edgar; Eng, Maria; McGrath, Janet; Kaawa-Mafigiri, David; Mugyenyi, Peter; Sethi, Ajay K. (AIDS care, 2020)
Adherence to antiretroviral therapy (ART) is critical in order to achieve viral suppression. We designed an intervention, Mobile Antiretroviral Therapy and HIV care (MAP-HC) in rural southwestern Uganda aimed to reduce travel distance and hypothesized that MAP-HC would improve ART adherence and rates of viral load suppression. The study was conducted at two district hospitals, among patients who lived >5 km from the hospital. For each hospital, we identified 4 health centers in the catchment area to serve as site for the mobile pharmacy. Each site was visited once a month to provide ART refills and adherence counseling. We measured patient waiting time, adherence and viral load suppression before and after the intervention. The proportion of patients who missed an ART dose in the last 30 days dropped from 20% to 8.5% at 12 months post-intervention (p = 0.009) and those with detectable viral load dropped from 19.9% to 7.4% (p = 0.001), however, mean waiting time increased from 4.48 to 4.76 h (p = 0.13). Mobile pharmacy intervention in rural Uganda is feasible and resulted in improvement in adherence and viral load suppression. Although it did not reduce patient waiting time at the clinic, we recommend scale-up in rural areas where patients face transportation challenges.
Keywords: Antiretroviral, adherence,rural,Uganda,mobile,pharmacy